2010
DOI: 10.1038/cmi.2010.4
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy-mediated modulation of inflammatory cytokine production by Epstein–Barr virus-infected nasopharyngeal carcinoma cells

Abstract: Nasopharyngeal carcinoma (NPC) is a malignant disease associated with Epstein-Barr virus (EBV) infection. This study aims to examine the effects of EBV infection on the production of proinflammatory cytokines in NPC cells after the Zn-BC-AM photodynamic therapy (PDT) treatment. Cells were treated with the photosensitiser Zn-BC-AM for 24 h before light irradiation. Quantitative ELISA was used to evaluate the production of cytokines. Under the same experimental condition, HK-1-EBV cells produced a higher basal l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 16 publications
0
29
0
Order By: Relevance
“…Of late, therapeutics targeting the host immune system is increasingly being recognized as the most prominent approach to treatment of cancer. 13 One such approach is the use of PDT as the preferred choice of cancer therapy in the twenty-first century, which has been proven to be a potent therapeutic approach for various cancers. 4 The ability of PDT to specifically recognize and selectively destruct cancer cells while leaving the rest of the body's normal cells unharmed indeed is considered to be a milestone ground-breaking development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of late, therapeutics targeting the host immune system is increasingly being recognized as the most prominent approach to treatment of cancer. 13 One such approach is the use of PDT as the preferred choice of cancer therapy in the twenty-first century, which has been proven to be a potent therapeutic approach for various cancers. 4 The ability of PDT to specifically recognize and selectively destruct cancer cells while leaving the rest of the body's normal cells unharmed indeed is considered to be a milestone ground-breaking development.…”
Section: Discussionmentioning
confidence: 99%
“…12 The phototoxic reaction following HY-PDT initiates the release of proinflammatory mediators by triggering the release of interleukin (IL)-1 α , IL-1 β , Interferon (IFN)- γ , IL-6, tumor necrosis factor (TNF)- α and certain other chemokines that provoke a strong inflammatory response in PDT-treated tumor cells. 13 Of note, IL-6, a pleiotropic cytokine implicated with barrier functions, is reported to trigger Th17 expansion. Furthermore, it is believed to have a paramount role in antitumor immunity at the site of inflammation owing to its neutrophil-mobilizing functions.…”
mentioning
confidence: 99%
“…Increased serum levels of GDF-15 due to its secretion by tumour cells is a marker of various types of cancer [60,61] and was in correlation with poor outcome and patient survival [61,62]. HY-PDT initiates release of cytokines and chemokines that provokes a strong inflammatory and antitumour immune response [63,64]. On the other hand, an inhibitory effect of GDF-15 on the tumour-specific immune response was described [59].…”
Section: Discussionmentioning
confidence: 98%
“…Koon et al 2010 showed that IL-8 production was down-regulated after Zn-BC-AM PDT in Epstein-Barr virus-infected nasopharyngeal carcinoma cells. This suggests that Zn-BCAM PDT might indirectly reduce tumor growth by lessening IL-8 secretion 57 .…”
Section: Effects Of the Immune System On Pdt For Cancermentioning
confidence: 97%
“…The complement system causes the release of pro-inflammatory cytokines such as IL-1β, IL-6, IL-8, IL-10, TNF-α, thromboxane, histamine, prostaglandins, leukotrienes, G-CSF and coagulation factors 8, 37, 57 . The release of thromboxane affects endothelial cells, causing them to shut down the microvasculature, leading to post-irradiation tumor ischemia 58, 59 .…”
Section: Effects Of the Immune System On Pdt For Cancermentioning
confidence: 99%